(untitled) (Fiep Bulletin - online, 2016)
The study aimed to evaluate and verify issues related to body image and food, geared to female bodybuilders. For the study, there was the application of EAT-26 questionnaire, which is an instrument of self-report consists of 26 questions to assess the attitudes and typical of anorexia behavior and the BSQ (Body Shape Questionnare), composed for 34 issues to examine the distorted body image. The sample consisted of 10 regular practitioners of weight training, and as a result it was shown that the BSQ questionnaire all participants had an average of answers without any serious change being that two women showed no disorder, five had mild body image disorder and three They had a mean body image disorder. You EAT-26 all the participants presented according to score some kind of body image disorder.